Effect of Milk Fat Concentration on Fat Crystallization of Palm Oil‐Based Shortenings. (26th October 2020) - Nguyen, Viet; Rimaux, Tom; Truong, Vinh; Danthine, Sabine; Dewettinck, Koen; Van Bockstaele, Filip
Abstract: The effect of different dosages of anhydrous milk fat (AMF) (25%, 50% and 75%, w/w) on shear‐crystallization of fat blends made of refined palm oil, refined palm stearin, and rapeseed oil was studied. Classical techniques as differential scanning calorimetry (DSC), pulsed field gradient nuclear magnetic resonance (pfg‐NMR), rheometer, and X‐ray diffraction (XRD) were applied to evaluate the crystallization kinetics of fat blends as well as the fat compatibility between components in rapid cooling (15 °C min −1 ), isothermal crystallization (at 15 °C), and storage (5 °C). Obtained results revealed that the mixtures of palm oils and milk fat had a low compatibility. The co‐crystallization between triacylglycerols (TAG) of milk fat and of palm oil occurred during isothermal crystallization and storage resulting in slower crystallization kinetics and the formation of some eutectic mixtures.